2021
DOI: 10.1115/1.4050391
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Film Cooling Using Time-Resolved Stereo Particle Image Velocimetry

Abstract: In the present study an existing test rig at the Institute of Thermal Turbomachinery (ITS), Karlsruhe Institute of Technology (KIT) designed for generic film cooling studies is adopted to accommodate time resolved stereoscopic particle image velocimetry measurements. Through a similarity analysis the test rig geometry is scaled by a factor of about 20. Operating conditions of hot gas and cooling air inlet and exit can be imposed that are compliant with realistic engine conditions including density ratio. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The test section was adapted to accommodate stereoscopic Particle Image Velocimetry Measurements (SPIV) (Stichling et al, 2021) capturing the field of view (FOV) ➆ indicated by the green area in Figure 1a. The SPIV measurement setup is detailed in Figure 1b using a top view on the hot gas channel of the test section from Figure 1a.…”
Section: Test Section and Measurement Setupmentioning
confidence: 99%
“…The test section was adapted to accommodate stereoscopic Particle Image Velocimetry Measurements (SPIV) (Stichling et al, 2021) capturing the field of view (FOV) ➆ indicated by the green area in Figure 1a. The SPIV measurement setup is detailed in Figure 1b using a top view on the hot gas channel of the test section from Figure 1a.…”
Section: Test Section and Measurement Setupmentioning
confidence: 99%